Manajemen Krisis Humas (Perum BULOG) dalam Kasus Demurrage Impor Beras - Juliyanti, Syalwa; Agustini, Vilya Dwi; Khotimah, Wininda Qusnul (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
When a crisis occurs in a company, the position of Public Relations becomes the center of how the company takes action to maintain its reputation and positive image. Some time ago, Perum BULOG was in the spotlight in the case of rice import demurrage. The descriptive qualitative method was used as a research with data collection in the form of participatory observation, in-depth interviews and literature reviews. The results of the study found that Perum BULOG attempted to deal with this crisis by providing an open explanation to the public and stakeholders regarding the causes of the rice import demurrage case and the mitigation steps that have been and will be taken.